Cover Picture: A 3D Nanostructured Hydrogel‐Framework‐Derived High‐Performance Composite Polymer Lithium‐Ion Electrolyte (Angew. Chem. Int. Ed. 8/2018). Issue 8 (2nd February 2018) - Bae, Jiwoong; Li, Yutao; Zhang, Jun; Zhou, Xingyi; Zhao, Fei; Shi, Ye; Goodenough, John B.; Yu, Guihua
Abstract : 3D nanostructured ceramic frameworks …. … improve the performance of composite polymer electrolytes for lithium batteries. In their Communication onpage 2096 ff. G. Yu et al. report a 3D nanostructured hydrogel‐derived ceramic framework, which was integrated with a polymer to create a flexible electrolyte membrane in which the 3D framework forms a percolated network. The continuous interphase on the framework improves the Li‐ion conductivity and the high ceramic content also increases electrochemical and thermal stability.